2020
DOI: 10.3389/fmicb.2020.01586
|View full text |Cite
|
Sign up to set email alerts
|

A Zinc-Dependent Metalloproteinase of Brucella abortus Is Required in the Intracellular Adaptation of Macrophages

Abstract: Brucella abortus is a pathogen that survives in macrophages. Several virulence factors participate in this process, including the open reading frame (ORF) BAB1_0270 codifying for a zinc-dependent metalloproteinase (ZnMP). Here, its contribution in the intracellular adaptation of B. abortus was analyzed by infecting RAW264.7 macrophages with the mutant B. abortus Δ270 strain. Results showed that this ZnMP did not participated in either the adherence or th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 64 publications
0
15
0
Order By: Relevance
“…A search in the Toxin-Antitoxin Database TADB2.0 [ 33 ] allowed us to identify at least four potential type II TA systems present in the chromosome I of B. abortus biovar 1 strain 9-941 ( , accessed on 29 August 2023) and B. abortus strain 2308 ( , accessed on 29 August 2023) ( Table 1 ). One of these TA systems is composed of the ZnMP (toxin) coded in the ORF BAB1_0270 (WP_002965518.1) present in a genomic island called “genomic island 3”, which is shared by some Brucella species, such as B. abortus 2308 and 9-941 strains [ 31 , 32 , 34 ]. This protein is homologous to the ImmA/IrrE metalloproteinases family, which is characterized by conserved domains COG2856 and motif HEXXH (pfam06114).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A search in the Toxin-Antitoxin Database TADB2.0 [ 33 ] allowed us to identify at least four potential type II TA systems present in the chromosome I of B. abortus biovar 1 strain 9-941 ( , accessed on 29 August 2023) and B. abortus strain 2308 ( , accessed on 29 August 2023) ( Table 1 ). One of these TA systems is composed of the ZnMP (toxin) coded in the ORF BAB1_0270 (WP_002965518.1) present in a genomic island called “genomic island 3”, which is shared by some Brucella species, such as B. abortus 2308 and 9-941 strains [ 31 , 32 , 34 ]. This protein is homologous to the ImmA/IrrE metalloproteinases family, which is characterized by conserved domains COG2856 and motif HEXXH (pfam06114).…”
Section: Resultsmentioning
confidence: 99%
“…This evidence demonstrates that several regulatory factors participate in the adaptation of B. abortus during its intracellular lifecycle in professional and non-professional phagocytic cells. Interestingly, our group described the roles of a zinc-dependent metalloproteinase (ZnMP), which forms an operon with an HTH-Xre regulator, constituting a putative type II TA system in B. abortus [ 31 ]. Results showed that deletion of ORF BAB1_0270 (ZnMP) significantly affected the capacity of this pathogen to survive under acidic conditions, to escape from phagolysosomes to reach its replicative niche in ER-derived vesicles, to survive within phagocytic cells and to colonize mice tissues [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several virulence factors determine Brucella survival in macrophages, including zinc-dependent metalloproteinase (ZnMP). Its deletion causes an increase in the co-localization of bacteria with phagosomal Cts D, reducing intracellular replication of the pathogen within RAW 264.7 cells (Goḿez et al, 2020). Importantly, B. abortus persistence in macrophages is associated with the presence of anti-inflammatory cytokine, IL-10 (Xavier et al, 2013).…”
Section: Brucella Abortusmentioning
confidence: 99%